2012
DOI: 10.1021/es204322c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Distribution and Stable Carbon Isotopic Composition of Dicarboxylic Acids, Ketocarboxylic Acids, and α-Dicarbonyls in Size-Resolved Atmospheric Particles From Xi’an City, China

Abstract: Size-resolved airborne particles (9-stages) in urban Xi'an, China, during summer and winter were measured for molecular distributions and stable carbon isotopic compositions of dicarboxylic acids, ketocarboxylic acids, and α-dicarbonyls. To our best knowledge, we report for the first time the size-resolved differences in stable carbon isotopic compositions of diacids and related compounds in continental organic aerosols. High ambient concentrations of terephthalic (tPh, 379 ± 200 ng m(-3)) and glyoxylic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 43 publications
(70 reference statements)
10
127
3
Order By: Relevance
“…However, our study instead revealed higher 1,4-phthalic acid in average (28.2 ng/m 3 ) than 1,2-phthalic acid (23.9 ng/m 3 ), the same as those reported in the polluted city sites, such as Chennai in India and Xi'an in China (Fu et al, 2010;Wang et al, 2012a). The levels of 1,4-phthalic acid and 1,2-phthalic acid quite approximated those reported in China and India, but were higher than those reported in USA.…”
Section: Levels and Compositionssupporting
confidence: 78%
See 2 more Smart Citations
“…However, our study instead revealed higher 1,4-phthalic acid in average (28.2 ng/m 3 ) than 1,2-phthalic acid (23.9 ng/m 3 ), the same as those reported in the polluted city sites, such as Chennai in India and Xi'an in China (Fu et al, 2010;Wang et al, 2012a). The levels of 1,4-phthalic acid and 1,2-phthalic acid quite approximated those reported in China and India, but were higher than those reported in USA.…”
Section: Levels and Compositionssupporting
confidence: 78%
“…In this study, 1,4-phthalic acid was found to be significantly correlated with 1,3,5-triphenylebenzene (r = 0.70, p < 0.01), which is a specific marker for the open-burning of plastics (Simoneit et al, 2005). This source of 1,4-phthalic acid can largely explain its higher levels in many Asian cities (Fu et al, 2010;Ho et al, 2010;Wang et al, 2012a) and its rare occurrence in aerosols from oceans and the Arctic (Narukawa et al, 2002;Simoneit et al, 2004). The quite different spatial patterns of 1,4-phthalic acid comparing to the secondarily formed 1,2-phthalic acid, as well as significant correlation between 1,4-phthalic acid and EC (r = 0.59, p < 0.01; Table 2), also supports that 1,4-phthalic acid was a primary pollutant.…”
Section: Source Attribution 231 Source Identificationmentioning
confidence: 50%
See 1 more Smart Citation
“…WSOC in the urban atmospheric presented a predominance in the fine mode with a small peak in the coarse mode during the nonevent, in contrast to a unimodal pattern of WSIC, which is dominant in the coarse mode ( Fig. 9a-d from photochemical oxidation of organic gases (Agarwal et al, 2010;Ram and Sarin, 2010;Salma et al, 2007;Wang et al, 2012a;Yu et al, 2004Yu et al, , 2005. Moreover, biomass burning is also an important source of WSOC.…”
Section: Size Distribution Of Wsoc Wsic and Wson In Xi'anmentioning
confidence: 98%
“…In each spring and early summer surface dust in Gobi desert region is brought about by front cold systems and the Mongolian cyclonic depression and transported into the downwind areas including North America (Leaitch et al, 2009;Seinfeld et al, 2004;VanCuren and Cahill, 2002). During transport mineral dust can internally mix with secondary compounds such as ammonium sulfate, ammonium nitrate, carboxylic acids, nitrogen-containing organics and sea salt by coagulation, cloud-processing and heterogeneous reactions (Geng et al, 2009;Seinfeld et al, 2004;Sullivan et al, 2009a;Tobo et al, 2010;Wang et al, 2012a;Zamora et al, 2011;. These processes modify the physicochemical properties of the airborne aerosols containing dust, exerting a significant impact on the downwind atmospheric environment (Dillner et al, 2006).…”
Section: G H Wang Et Al: Impact Of Gobi Desert Dust On Aerosol Chementioning
confidence: 99%